MENJADI GURU SD YANG MEMILIKI KOMPETENSI PERSONAL-RELIGIUS MELALUI PROGRAM ONE DAY ONE JUZ (ODOJ) - Aeni, Ani Nur (Mimbar Sekolah Dasar, 2015)
Teachers are professional educators who are bound by the four competencies (pedagogical, professional, personal, and social. In the study of Islamic education competence is referred to as personal-religious and professional-religious. In an attempt to give birth to a teacher who has a personal competency-religious then one way that can be achieved is through the one Day one Juz (ODOJ). ODOJ is a program of recitations of the Quran one day one juz, so that the activities of recitations through this program will be able toÂ finish Al-Quran at least one a month. This program will provide impact (atsar) forÂ everyone's perpetrators. Including teachers, elementary school teachers are expected to figure there are teachers who have the Qur'anic morality.Keywords: personal-religious, professional-religious, One Day One Juz (ODOJ).